A brief history of the Australasian Neuroscience Society. Issue 4 (2nd October 2022) - Abraham, Wickliffe C.; Geffen, Laurence B.; McLachlan, Elspeth M.; Richards, Linda J.; Rostas, John A. P.
ABSTRACT: The collective efforts of Australasian neuroscientists over the past 50 years to forge a binational presence are reviewed in this article. The events in the 1970s leading to the formation of an informal Australian Neurosciences Society are discussed in the context of the international emergence of neuroscience as an interdisciplinary science. Thereafter, the establishment in 1980 of the Australian Neuroscience Society, subsequently renamed as the Australasian Neuroscience Society (ANS), is described. The achievements of ANS—including its active role in developing national, regional, and global cooperation to promote neuroscience—are chronicled over successive decades, followed by a discussion of the future challenges facing the society and its associated neuroscience institutions.